Revista de Saúde Pública in scientific publications on Violence and Health (1967-2015) - Lilia Blima Schraiber; Claudia Barros; Ana Flávia Pires Lucas d’Oliveira; Maria Fernanda Tourinho Peres (Revista de Saúde Pública)
ABSTRACT This article retrieved the publications from the Revista de Saúde Pública journal (from 1967 to 2015) on violence and health, on the SciELO and PubMed bases, by searching for the terms “violence”, “suicide”, “aggression”, “bullying”, and “external causes”, registered in any part of the text. We found 130 articles (the first one published in 1974). We observed: increase of publications over time, with decrease in the last five years; similar production volume in lethal and non-lethal violence; later publication of the latter; few studies in qualitative research; mostly descriptive production; and visualization of the problem more by the acts than by contexts or motivations and aggressors. Social markers were little approached, appearing, from largest to smallest frequency, social class, gender, race/ethnicity, and generation. Human rights were little used and only recently used as analytical framework, connected more to gender than to social class. Although Revista de Saúde Pública has registered the theme in its publications, consolidating it as scientific production line, there is still great explanatory theoretical rarefaction and little intersectionality between violence, social inequalities, and human rights.